A discussão de assuntos complexos na perspectiva de professores e alunos: The Road (Not) Taken - Neves, Rogério da Costa (2011)
The objective of this research is to investigate and understand the phenomenon of complex issue treatment held during English classes in a public school in Rio de Janeiro taking into consideration students and teachers perspective. Complex issues are topics brought to the school environment through the use of determined materials, students request and teachers decision. These issues when dealt with allow numerous unfolding that may lead teachers and students to discuss topics that do not find in society a clear and defined positioning. Thus, they may arouse unexpected reactions from the part of those involved directly or indirectly in their treatment within school boundaries. This study was carried out with an initial group of 30 teachers who declared to hold this type of activity with their students. From this initial group, a focal group was created with 18 participants. There were also 37 students involved in this study who were able to discuss these issues during their English classes. With the intent of better understanding what really happened in my teaching practice I examined the official Brazilian documents (PCN, 1998; PCN-LE, 1998; OCEM, 2006) and also school documents (PPP, 2000). Based on these documents I tried to understand the paradigmatic changes that had taken place and that made realize the unsuitability of my own background education in relation to my present teaching practice. This led me to the study of the complexity theory (Morin, 1997/2008; Moraes, 1997/2006; Mariotti, 2007) which served as a theoretical-methodological basis for this research, the grounds on which all actions, interactions, and retroactions of lived experiences took place. In search of a better understanding of my own practice I also made use of the global/localized knowledge concept (Canagarajah, 2004; Celani, 2004). The objective in using questionnaires, face-to-face interviews, e-mails, exchange of messages by means of a social network and Moodle was to discuss the relevance, appropriateness, frequency and objectives of complex issue treatment. I was able to describe and interpret the phenomenon making use of a hermeneutic-phenomenological methodological approach (van Manen, 1990; Freire, 2003, 2007). The interpretation of the phenomenon revealed the existence of only one phenomenon in which students and teachers present their perspectives on what it is to discuss complex issues. Teachers in their texts brought about four themes: precaution, choice, absence and the other. These themes signal to a number of precautions taken and choices made by teachers when developing these activities. Teachers also reveal what they perceive as to be inexistent, or insufficient when dealing with these issues. Students texts unveiled three themes: impressions, changes and the other. These themes comprise what they believe to be the role of school and the results that could be achieved by activities like the ones developed during this research